2014
DOI: 10.1074/jbc.m114.579821
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Glucosyltransferase That Converts Hydroxymethyluracil to Base J in the Trypanosomatid Genome

Abstract: Background: Base J regulates Pol II transcription in trypanosomatids and is synthesized in two steps involving DNA hydroxylation and glucosylation. Results: JGT catalyzes the transfer of glucose from uridine diphosphoglucose to hmU in DNA. Conclusion: JGT is the glucosyltransferase involved in base J synthesis. Significance: JGT is the first known glucosyltransferase that modifies eukaryotic DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 47 publications
2
59
0
Order By: Relevance
“…After submission of this manuscript, a study published elsewhere [21] confirmed the complete loss of J after knockout of Tb927.10.6900 in T. brucei and that reintroduction of the gene into Tb927.10.6900 -null T. brucei restored J synthesis. That study also showed that reduction of HmdUGT mRNA by RNAi causes reduced J and increased HOMedU levels and that the glucosyltransferase uses uridine diphosphoglucose to transfer glucose to HOMedU.…”
mentioning
confidence: 65%
“…After submission of this manuscript, a study published elsewhere [21] confirmed the complete loss of J after knockout of Tb927.10.6900 in T. brucei and that reintroduction of the gene into Tb927.10.6900 -null T. brucei restored J synthesis. That study also showed that reduction of HmdUGT mRNA by RNAi causes reduced J and increased HOMedU levels and that the glucosyltransferase uses uridine diphosphoglucose to transfer glucose to HOMedU.…”
mentioning
confidence: 65%
“…1c). JBP1 and 2 are capable of oxidizing thymine to both 5-hydroxymethyluracil (hmU) and 5-formyluracil, though a glucosyltransferase normally diverts hmU to form base J as part of the trypanosome’s mechanism for immune evasion 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…In trypanosomatid parasites such as Leishmania and Trypanosoma , sugar-activating enzymes - including UGP - represent attractive drug targets since many vital processes within the parasites utilize UDP-Glc and UDP-Gal38394041. However, drugs targeting structurally conserved elements (i.e.…”
Section: Discussionmentioning
confidence: 99%